2020
DOI: 10.1002/onco.13578
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Changes in Oncology Care Pathways During the COVID-19 Pandemic: The French ONCOCARE-COV Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic may have affected cancer management. We aimed to evaluate changes in every oncology care pathway essential steps, from screening to treatment during the pandemic. Monthly oncological activity differences between 2019 and 2020 (screening tests, histopathological analyzes, multidisciplinary tumor board meetings (MTMB), diagnostic announcement procedures (DAP), and treatments) were calculated in two French areas experiencing different pandemic's intensity (Reims an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 10 publications
4
50
2
Order By: Relevance
“…With particular relevance to our study, it should be noted that an observational Taiwanese cancer registry study 34 , based on 39,000 newly identified CRC cases, reports that the risk of death increases significantly relative to the delay between diagnosis and treatment: to an interval ≤ 30 days, for 31–150 days: HR 1.51; (95% CI 1.43 to 1.59); for ≥151 days: HR 1.64; (95% CI 1.54 to 1.76). The French ONCOCARE-COV study confirmed a reduction in terms of CRC FIT screening (−86%), CRC biomolecular somatic analyses (−59%), and new patients files discussed in multidisciplinary tumor board meeting (−39%) during the 3-month lockdown period in 2020 compared with the same trimester in 2019 31 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…With particular relevance to our study, it should be noted that an observational Taiwanese cancer registry study 34 , based on 39,000 newly identified CRC cases, reports that the risk of death increases significantly relative to the delay between diagnosis and treatment: to an interval ≤ 30 days, for 31–150 days: HR 1.51; (95% CI 1.43 to 1.59); for ≥151 days: HR 1.64; (95% CI 1.54 to 1.76). The French ONCOCARE-COV study confirmed a reduction in terms of CRC FIT screening (−86%), CRC biomolecular somatic analyses (−59%), and new patients files discussed in multidisciplinary tumor board meeting (−39%) during the 3-month lockdown period in 2020 compared with the same trimester in 2019 31 .…”
Section: Discussionmentioning
confidence: 86%
“…While the lockdown was undoubtedly a necessity, it led to unintended consequences in the diagnosis of various cancers. While the pandemic has dramatically affected all aspects of the cancer care pathway those especially affected are screening, diagnosis and surgical treatment 31,32,4 . For instance, De Vincentiis et al have reported that the number of cancer diagnoses in Italy decreased by 39% in the first semester of 2020, compared to the average number recorded in 2018 and 2019 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A general reduction in overall cancer care in several countries in the same period has been observed. Indeed, in the UK, urgent referrals and chemotherapy for any cancer, including oropharynx cancer, decreased by 70% and 40%, respectively, 25 while reductions by 9% in chemotherapy, 16% in radiotherapy, and 30% in surgery were observed in France 26 . Among patients with cancer under treatment in the Netherlands, treatment or follow‐up was postponed or cancelled in 11% of individuals and changed into phone/video counselling in 18% 27 .…”
Section: Figurementioning
confidence: 99%
“…The data from June were the most up to date when this study was carried out. Data on hospitalizations that occurred between April and June of 2016, 2017, 2018 and 2019 were also gathered from SIH-SUS for comparison, by Brazilian State of patients' residences-Brazil is divided into 26 States and one Federal District. To obtain the hospitalization rates, we divide the monthly number of hospitalizations due to oral and oropharyngeal cancer in each State by its population and multiply the result by 100 000.…”
mentioning
confidence: 99%
“…The impact of the reorganization of healthcare systems during the first wave of the COVID-19 pandemic was major on cancer care pathways [5] , [6] , [7] , [8] . The French ONCOCARE-COV study confirmed a reduction in terms of colon cancer screening (−86%), histopathological (−48%) and biomolecular (somatic and germinal) (−69%) analyses, oncology announcement consultations (−54%), oncogeriatric evaluations (−86%) and new patients files discussed in multidisciplinary tumor board meeting (MTBM) (−39%) [5] . The decrease in cancer treatment was also significant concerning surgery (−30%) and to a lesser extent for radiotherapy (−16%) and chemotherapy (−9%); all clinical research trials were stopped for 3 months [5] .…”
mentioning
confidence: 99%